2017
DOI: 10.1186/s40100-017-0073-1
|View full text |Cite
|
Sign up to set email alerts
|

Japanese consumer preferences for additive-free wine labeling

Abstract: Consumers have recently become more concerned about food additives and food safety. Since its first meeting on September 17, 2003, the Risk Communication Expert Committee has studied and discussed the ideal methods to communicate risk related to food safety issues in response to a Food Safety Commission request. However, there are only a few case studies that actually apply to risk communications. This study aims to analyze consumer preferences for antioxidantfree wine and suggest a tool for risk communication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
(15 reference statements)
1
9
0
Order By: Relevance
“…This highlights how the consumers' interest towards natural wine is strongly associated with the desire to consume foods and beverages that do not contain additives and are unprocessed and the desire to preserve the environment and natural resources. With specific reference to health attitudes, measured through NPI attitude scale, our results are consistent with several empirical evidences, which showed a growing attention of consumers towards health aspects, also for the wine, and willing to pay a premium price (D'Amico et al, 2016;Amato et al, 2017;Kubota et al, 2017). Indeed, sustainable wines, among which the organic and natural ones, are considered to be more directly linked to a healthy life style than their conventional counterparts (Galati et al, 2019;Sirieux and Remaud, 2010).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…This highlights how the consumers' interest towards natural wine is strongly associated with the desire to consume foods and beverages that do not contain additives and are unprocessed and the desire to preserve the environment and natural resources. With specific reference to health attitudes, measured through NPI attitude scale, our results are consistent with several empirical evidences, which showed a growing attention of consumers towards health aspects, also for the wine, and willing to pay a premium price (D'Amico et al, 2016;Amato et al, 2017;Kubota et al, 2017). Indeed, sustainable wines, among which the organic and natural ones, are considered to be more directly linked to a healthy life style than their conventional counterparts (Galati et al, 2019;Sirieux and Remaud, 2010).…”
Section: Resultssupporting
confidence: 87%
“…In fact, while some authors find a scarce willingness, among consumers, to pay for wines without the addition of sulfites (Costanigro et al, 2014), others note a high WTP for these wines (D'Amico et al, 2016) probably because they reported discomfort following the wine consumption with this ingredient added (Amato et al, 2017). Similarly, the provision, on the label, of information on the antioxidant content in the wine negatively influences the WTP of consumers, especially those who recognize food additive dangers (Kubota et al, 2017). The influence of wine ingredients on the WTP of consumers has been demonstrated also by Ghvanidze et al, (2017), according to which, consumers who are concerned about healthy diets were found to be more willing to trade off product attributes regarding low carbohydrates in wine and a WTP for such category of wine.…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…Specifically, the literature on consumer wine choices has focused on 'clean' labels related to aspects such as organic, biodiversity friendly, and biodynamic wine production processes [69][70][71][72], harvesting techniques, and the absence of additives [73][74][75][76]. This literature confirms the link between naturalness and health [77,78].…”
Section: Introductionmentioning
confidence: 66%
“…On the other hand, lack of familiarity with food ingredients increases the perceived risks by consumers (Aschemann-Witzela, Varelab, & Peschela, 2019). Kubota, Sawano, & Kono (2017) find that the awareness of consumers on health risks of wine additives and their knowledge on food and wine processing reversely affect their preferences. Consumers who are aware of the dangers of wine additives prefer antioxidant-free wines.…”
Section: Food Additivesmentioning
confidence: 93%